2008
DOI: 10.4028/www.scientific.net/ddf.278.55
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Local Structure and the Spin Hamiltonian Parameters for Co<sup>2+</sup> in CaTiO<sub>3</sub>

Abstract: The local structure and the spin Hamiltonian parameters g factors gi (i =x, y and z) and the hyperfine structure constants Ai for Co2+ in orthorhombic CaTiO3 are theoretically investigated from diagonalization of 6 × 6 energy matrix within the 4T1 ground state for a 3d7 ion in orthorhombic symmetry. In the calculations, the contributions from the admixtures of various J states (J=1/2, 3/2, 5/2), the ligand orbitals and spin-orbit coupling and the fourth-order orthorhombic field parameter, which were usually ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…It is proved that taking into account these factors is significant, the relevant detailed discussion may reference our previous work. [22,23] In summary, the off-displacement value ∆𝑅 ≈ 0.023 nm for Co 2+ ions in SrO is obtained by fitting the calculated 𝑔 factors to the observed values, it is very close to the value ∆𝑅 ≈ 0.021 nm in previous works, the calculated 𝑔 factors based on the off-center displacement show good agreement with the experi-086103-3 mental data. It is necessary to consider the contributions from 𝐽-admixtures, the fourth-order term 𝐷 𝜂 of rhombic crystal-fields and ligand orbital and spinorbit coupling interactions which are usually neglected in the course of the calculation of 𝑔 factors.…”
supporting
confidence: 85%
“…It is proved that taking into account these factors is significant, the relevant detailed discussion may reference our previous work. [22,23] In summary, the off-displacement value ∆𝑅 ≈ 0.023 nm for Co 2+ ions in SrO is obtained by fitting the calculated 𝑔 factors to the observed values, it is very close to the value ∆𝑅 ≈ 0.021 nm in previous works, the calculated 𝑔 factors based on the off-center displacement show good agreement with the experi-086103-3 mental data. It is necessary to consider the contributions from 𝐽-admixtures, the fourth-order term 𝐷 𝜂 of rhombic crystal-fields and ligand orbital and spinorbit coupling interactions which are usually neglected in the course of the calculation of 𝑔 factors.…”
supporting
confidence: 85%
“…Hence, the parameter ( ) B 0 4 3 determined from the fit of χ mol (T) is the more reliable one. To our knowledge, apart from the studies of Lu et al [43] on the Spin Hamiltonian parameters of Co 2+ in CaTiO 3 , there are no further reports on the ligand field parameters of Co 2+ incorporated at B site of a perovskite. Lu et al [43] reported a 10Dq value of about 14 000 cm −1 which corresponds only roughly with the 10Dq value of 20 000 cm −1 obtained from our susceptibility data (section 3.4.1).…”
Section: Analysis Of the Epr G Tensor Of Comentioning
confidence: 89%
“…To our knowledge, apart from the studies of Lu et al [43] on the Spin Hamiltonian parameters of Co 2+ in CaTiO 3 , there are no further reports on the ligand field parameters of Co 2+ incorporated at B site of a perovskite. Lu et al [43] reported a 10Dq value of about 14 000 cm −1 which corresponds only roughly with the 10Dq value of 20 000 cm −1 obtained from our susceptibility data (section 3.4.1). CONCORD also allows the simultaneous fit of the ΔE values for different directions of the magnetic field, which can be applied for Co 2+ (Q-band) was fitted.…”
Section: Analysis Of the Epr G Tensor Of Comentioning
confidence: 89%